Early stages of surface alteration of soda-rich-silicate glasses in the museum environment. (October 2018) - Rodrigues, Alexandra; Fearn, Sarah; Palomar, Teresa; Vilarigues, Márcia
Highlights: Three types of soda-rich historical fire-polished glasses show different alteration. Environmental water availability contributes to the increase of the altered layer. High relative humidity enhances the formation of Na-enriched areas on the surface. Glass composition has a strong influence on the kinetics of surface alteration. Abstract: This paper studied the alteration of three soda-rich-silicate glass types ( Cristallo, façon-de-Venise and soda-lime silicate). Replica samples were exposed to different environments simulating museum-like conditions – room temperature and different relative humidities (RH). Results were analysed by SIMS, μ -FTIR, Optical Microscopy and Optical 3D profilometry. Cristallo appears as the most vulnerable, whilst the soda-lime glass appears as the most resistant to the environmental deterioration. The thickness of the altered layer is proportional to the time of exposure and to the RH of the surrounding atmosphere. From the results obtained, the glass composition and the water available and adsorbed to the surface strongly influence the kinetics of the surface alteration.